Women Attribute and Household Level Factor on Women's Empowerment - Neneng Miskiyah; Sari Lestari Z Ridho; Hadi Jauhari; Keti Purnamasari (Media Ekonomi dan Manajemen, 2021)
Empowerment is an important strategy in increasing the role and opportunities of women in improving their economy and is an effort to increase and actualize their potential so that they are more able to be independent and work, and are more appreciated. This study aims to analyze the probability of empowering women in the songket craft business, testing and analyzing the variable women attribute and household level factor on women's empowerment . Tests are carried out using binary logistic regression .  The results showed that the variables of age, education, and work experience had a significant effect on women's empowerment. The policy implication of the results of this study is that there needs to be more serious attention and involvement from the  government and other institutions in coaching women songket craftsmen, and improving the quality of women through various activities to empower them through songket business activities.